The pole vault takeoff - Bussabarger, D. (Track Coach, 2016)
The thrust of the following section of my forthcoming book on the vault (co-written with Bruce Caldwell) is to question the so-called free takeoff or the model developed by Ukrainian coach Vitaly Petrov. The Petrov model, particularly his free takeoff concept, was simply a hypothesis with no basis in the real world when originally proposed. Petrov believed/ believes that fiberglass vaulters should take off like past rigid vaulters (particularly Warmerdam). That is, the fiberglass vaulter should takeoff "out" and emphasize jumping directly upward at the instant of takeoff in order to produce overhand rotation in the pole to move it to vertical. At the same time the vaulter should avoid bending the pole until he/she is airborne (this and taking off "out" are the most common ideas associated with the free takeoff). Petrov taught this technique to Bubka. Ironically even Sergey Bubka had difficulty executing a free takeoff consistently and very few if any other elite male vaulters employ/employed a free takeoff as proposed by Petrov. There are several critical problems with Petrov's free takeoff concept.